Stammereligioner: konversion til kristendom og hinduisme i Indien. Illustreret med eksempler fra santal- og bodostammerne i kolonitiden i Indien - Andersen, Peter Birkelund (Religionsvidenskabeligt Tidsskrift, 2015)
Based on case studies of conversion among the Santals and Bodos in Central India and Assam from 1867 to the 1930s it is argued that the European Christian missionaries to the tribal peoples overstated the importance of baptism and did not fully understand the rationality which the converts addressed their situation through. During the colonial period the converts to Christianity were far more open to mobility between different religious groups and far more elective between local and Christian religious traditions. These facts query the post-colonial resentment of the acts of the Protestant Christian missions during the colonial period as well as the larger approach to the colonial period in the school of ‘post-colonial studies’. In both cases due to the fact that the Indians living during the colonial period are denied the rationality they acted within. A note has been added post-release in the end of the article on the request of the author.